The IOT-Based Hydrogen Sulfide Monitoring at PT. Pertamina Geothermal Energy on Lumut Balai Area - Dasmen, Rahmat Novrianda; Muhammad Adrian Saputra (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2023)
Geothermal Power Plants produce electricity energy from geothermal sources found in geothermal wells. Inside the geothermal well there is H2S content which is a toxic gas that can cause death to humans when human exposed the H2S content for 500-700 ppm within 30-60 minutes. Based on several literacies, in this research, H2S sensor type MQ-136 was used to monitoring H2S content in the geothermal environment. The Internet of Things system is used to read data parameters as a tool to display PPM values on the LCD of the transmitter and receiver device, as well as Adafruit IO website for reading parameter sensor data.. To transmit data from the transmitter to the receiver, Lora Ra-01 AI Thinker is used. The focus of this research is to be able to remotely monitor H2S content through the Adafruit IO website, the highest data was read is 0.54 ppm and the lowest at 0 ppm. This equipment will give